Pemuridan Bagi Jemaat Penyandang Disabilitas - Innawati Teddywono (Sekolah Tinggi Theologia Nazarene Indonesia, 2020)
Abstract The church must play an active role in society by empowering its congregation, without exception the marginalized - persons with disabilities; who should have the same rights and opportunities, as well as equal treatment; empowered and involved in the ministry of the church, giving meaning to the lives of others and himself to the glory of God. It was undeniable that persons with disabilities experience discrimination in various fields of life, including church services. The research method used was qualitative; conducted in-depth and open observations, focused interviews, and selected interviews with selected informants. The research objective was to find a model of discipleship for congregations with disabilities in the M Malang Church. The findings of the research suggest that the model of discipleship in the M Malang church was a combination of equipping through teaching Christian values, building attitudes, and empowering the congregation. The pastor prioritizes empowerment with mission trip activities as a model of discipleship for congregations with disabilities.